Politics of indigenizing Brecht’s work in selected plays of Ajoka theatre in Pakistan - Kayani, Taimur (2018)
Transcultural theatrical adaptation has become an increasingly important and emerging domain of inquiry for scholars of language and literature because it illuminates points of contention, raises questions, problems and allows multiple perspectives to suggest answers to the contemporary issues. In this context, it is also a key issue and vigorous focus for dramatists and artists in storytelling due to its collaborative creative mode as a process, continuing popularity as a product. In recognition of above mentioned issue, Brecht’s canonical literary work and its indigenization in Pakistan offer a valuable transcultural adaptation study because it was performed through a radical theatre movement with a distinct dramaturgy and political philosophy in two different cultural contexts and historical frame of references. As the foremost representative of Brecht’s radical dramaturgy, in Pakistan since 1983, Ajoka theatre utilized these adaptations as socio-political spaces to challenge dominant discourse on the rise of dictatorship and capitalism in Pakistan. The study anchors the selected plays within their historical contexts, emphasizing the value regarding the plays themselves as historical documents. This study addresses this gap by exploring and examining the political dimension of these theatrical adaptations of Brecht selected works in light of Hutcheon’s theory of adaptation and New Historicism. The study comprised three separate sections. The first dealt with criticism of capitalist society, the second with the means of changing that society and third with the nexus between capitalism and dictatorship. This dissertation investigated the socio-political imperatives: the emergence of fundamentalist Martial Law regime, rise of capitalism with nexus between it and religion which necessitated the transcultural adaptation of selected Brecht’s plays thus confirmed Hutcheon’s assumption of historical intentionality that socio-political conditions also create the environment for adaptation and that the theory of adaptation should address that researched area of investigation. Secondly, it explored Brecht’s theatre adaptability to traditional Asian folk theatre and locate distinct transcultural adaptation process which made them new cultural products and thirdly, the study conducted new historicist study of selected Brecht plays and their adaptations with dictatorship and capitalism as a historical context, which revealed thought provoking findings, contradicted the previous researches which label them as ‘timeless pieces of literature’. The study revealed that Ajoka theatre’s continuous engagement with Brecht’s work is highly productive. Ajoka theatre has gained radical identity and an international reputation while Brecht’s canon has gained a new set of audience, dynamic Asian theatrical space and opportunity to propagate Brecht’s social and political philosophy. Finally, since majority of the current research look at political dimensions and social factors in Pakistan from the late 1970s onward have contributed towards Pakistan’s image as a terrorist land, particularly after 9/11, this dissertation provides a fresh look on the struggle of Pakistani nation as a vibrant, democratic and theatre loving nation.